Monitoring and Movement Detection of Patient Using Consecutive Frame Comparison Method (International Journal of Scientific Research and Management (IJSRM), 2017)
Detection of changes due to movement in a real time video is very important tool. Patient movement & monitoring system is a system that is used to detect movement changes in patient. Those changes may be either abnormal behavior or unusual changes made by the patient in the absence of doctor. This paper presents the method of patient movement monitoring system for those patients that are taking medical treatment in both local and foreign hospitals with the help of frames comparison approach. A lot of techniques have been proposed for this problem but the main problem that has been highlighted in this paper is that there are less number of experienced doctors and nurses in both local & foreign hospitals and the existing systems captures the whole movement in real time video which will lead to the wrong treatment. In this technique, we have to arrange a digital camera that will keep an eye on the patient only. This system will automatically save the changes movement by the patient only not by the whole real time video in the absence of doctor. These graphs can then be analysed by the doctor at a later point of time. This research work is very helpful for critical patients like coma patients, dialysis patients and for those who were on bed for a long period. Because in these conditions, a minor movement done by the patient is detected that plays an important role in their treatment.